Reliability of Rubrics in Mini-CEX - Lubna Siddiq, Anam Arshad, Muhammad Moin (Pakistan Journal of Ophthalmology, 2017)
Purpose: To study the reliability of rubrics in mini clinical exercise (CEX) in Ophthalmic examination. Study Design: Observational cross sectional study. Place and Duration of Study: Our study was conducted at the ophthalmological society of Pakistan, Lahore branch on Sep 17, 2015. Material and Methods: 16 raters were recruited from the candidates eligible for fellowship exit exam. All these raters were provided with a rubric to evaluate the clinical performance of cover/uncover (squint assessment) test. . Every rater gave scores (2-5) for 12 steps of the clinical examination. All scores were entered into SPSS version 20 and Cronbachs’ alpha coefficient of inter rater reliability and internal consistency of scores was determined. Results: 16 raters having age range from 26-35 years with mean age of 29.4 SD ± 1.99 took part in this study. Out of them 7 were male and 9 were female. The Cronbach Alpha (0.972) was found to be very significant after analyzing the scores of the sixteen raters in SPSS. The intra class correlation co-efficient was found to be .967. Descriptive statistics showed that sixteen raters gave a rating between 3.3 to 4.0 for each step of the rubric. Conclusion: Rubrics are effective in achieving a high inter rater reliability in mini-CEX and make it a very useful tool in assessment of clinical skills. Keywords: Rubrics, mini-CEX, inter rater reliability, variability